Analisis Pengaruh Citra Merek Dan Kepercayaan Merek Terhadap Loyalitas Merek Pada Brand Lokal Eiger Di Kabupaten Cianjur - Rachma, Adinda Meisya; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2025)
A study reveals the relationship between brand image and brand trust with brand loyalty for local brand Eiger products distributed in Cianjur Regency. The increasing nature tourism activities in the Cianjur area have driven higher demand for outdoor equipment, in line with the rapid development of the outdoor fashion industry in the country. Facing tight competition from various domestic and foreign brands, efforts to maintain consumer loyalty are key to success through the formation of a strong brand image and brand trust. Quantitative methods were chosen for data collection, with questionnaires as the main material distributed to Eiger user respondents in the Cianjur area. Statistical testing was applied to the collected data to measure the influence of brand image and brand trust indicators on brand loyalty dimensions. The results of the analysis proved a significant positive influence of both factors. The characteristics of consumers who view the image and trust in Eiger positively display a high level of loyalty, reflected in repeat purchasing patterns, willingness to recommend, and commitment to the brand. These findings highlight the urgency for companies to design strategies to strengthen brand image and brand trust as the main goal. The benefits obtained are in the form of maintaining customer loyalty amidst the increasingly competitive outdoor fashion industry. The problem of inter-brand competition can be addressed through the implementation of appropriate strategies, based on the findings of this study.